Study on China’s River Chief System: Development History, Security Governance Function and Improvement Prospects - Zhouda Zhan (Law and Economy, 2023)
The river chief system is an innovative institutional design in terms of ecological security governance of river basins in China. In modern China, the river chief system is first practiced in Changxing County of Zhejiang Province in 2003, and it is tested effective in the emergency management of Taihu Lake cyanobacteria in Wuxi of Jiangsu Province in 2007. After 2007, the river chief system begins to be widely promoted and gets authorized as a nationwide working model since 2016. China’s river chief system has the function of helping ecological security governance, which should be improved. The way to improve the function of the river chief system in the future can be to add as a special chapter on the river chief system into a piece of central legislation, or to formulate a special piece of administrative regulation on the river chief system, or to continue to provide provisions in the form of local legislation, no matter at the provincial or municipal level.